Habermas and Religion. Issue 3 (March 2016) - Sheedy, Matt
Abstract: At 86, Jürgen Habermas remains one of the most influential living social philosophers in the world. Since the 9/11 attacks, he has focused on the problem of religion in the public sphere and helped to popularize the term 'post‐secularism'. Despite this recent shift in his work, religion has always been a theme in his complex critical theory. In this paper, I trace the ways in which Habermas has situated religion over the span of his career, including significant shifts, and the ways in which his theory has been taken up by others. In conclusion, I point toward some directions for future engagement with his work in the study of religions.